Weaker today, stronger tomorrow: Peer learning and firm innovation after the great recession - Marina Traversa (Leibniz Institute for Financial Research SAFE, 2026)
Can a recession have a positive, long-term impact on firm innovation? A downturn represents an opportunity for firms to learn from their peers and try to understand the main drivers of resilience. If they deem R&D capital one of them, they may raise innovation in the following years, in order to be better shielded from future crisis. In this paper, I provide evidence of this effect in the aftermath of the Great Recession. I do so by assuming that firms learned from their best peers and by examining the characteristics of these companies. I first look at their level of R&D capital and find that firms with high-R&D best peers raised intangible investment 5 percent more than others after 2008. I then examine the top competitors' type of R&D capital and show that companies raised innovation only in the case of high-productivity (as opposed to high-product differentiation) best peers. Using alternative tests, I find a positive (negative) relationship between productivity (product differentiation) and company performance during the crisis, which supports the fact that companies learned from their peers and raised innovation only when they deemed it a source of resilience to the downturn. Finally, I examine whether the increase in innovation improved firm resilience and show that it did: companies raised sales growth, profitability and international recognition and were less likely to fail.
Keywords: G30; 330; Corporate Finance; Innovation; Learning; Resilience; Productivity; Product Differentiation